Electromagnetic wave shielding and mechanical properties of vapor-grown carbon nanofiber/polyvinylidene fluoride composite fibers - YÜKSEK, METİN (SAGE PUBLICATIONS LTD, 2020)
The demand for multifunctional requirements in aerospace, military, automobile, sports, and energy applications has encouraged the investigation of new conductive composite fibers. This study focuses on the development of Vapor-grown carbon nanofibers (VGCNFs) filled Polyvinylidene Fluoride (PVDF) composite fibers. Polyvinylidene fluoride (PVDF) reinforced with (1, 3, 5, and 8 wt.%) carbon nanofibers were produced as a masterbatch. The production of PVDF and PVDF/CNF composite fibers have been done successfully by using melt spinning processing technique. Conductive woven fabrics were produced with composite fibers on handloom machines to measure electromagnetic interference (EMI) shielding efficiency. Tensile strength of fibers increased with increase in CNF loading up to 3%. The tensile strength displayed a decrease of 5% and 8% CNF loading. Electromagnetic shielding effectiveness (EMSE) of woven fabrics with composite fibers were tested by using the coaxial transmission line method for planar materials standard that is based on ASTM D 4935-10. The electromagnetic shielding effectiveness of woven fabric which is consist of conductive composite fibers were increased with increasing CNFs loading and amount of fabric layers. It can be seen that the woven fabrics displayed between 2-10 dB and 2-4 dB EMSE values in the 15-600 MHz and 600-3000 MHz-frequency range, respectively. Nevertheless, it was observed that conductive filler content, dispersion, and network formation within the composite fibers were highly influent on the electromagnetic shielding effectiveness performance of the structures.
Keywords: Polyvinylidene fluoride; vapor-grown carbon nanofibers; electromagnetic shielding effectiveness; conductive composite fibers